IMPORTANCE-PERFORMANCE MATRIX ANALYSIS OF KOTA BHARU’S ISLAMIC CITY IMAGE - Hassan, Hasnina; Omar, Shida Irwana; Ahmad, Ghazali (PLANNING MALAYSIA, 2020)
In 2005, Kota Bharu as the Kelantan state capital in Malaysia was rebranded from a Cultural City to an Islamic City and projecting its image as an Islamic identity. Limited studies have been undertaken to assess city image from the perspective of visitors. Therefore, this paper aims to evaluate the perception of visitors on the importance and performance of the Islamic city image of Kota Bharu. Data were gathered using a self-administered survey questionnaire among domestic and international visitors in Kota Bharu in 2018. The questionnaire was prepared based on ten categories of Islamic Built Environmental factors, namely; natural environment, social need and human comfort, religious identity, tolerance, layout, elements of Jannah (paradise), intellectual and knowledge, cleanliness, economic system, and safety setting. The data were analysed quantitatively using partial least squares-structural equation modelling (PLS-SEM). The results revealed that visitors considered "Religious Identity" as the most important attribute which reached a satisfactory level, while other factors also needed to be addressed. The findings are expected to contribute to a better understanding of stakeholders in enhancing the image of Islam Bharu for management and marketing purposes.